Thermodynamic Work of High-Grade Uterine Prolapse Patients Undergoing Transvaginal Mesh Repair with Total Hysterectomy - Hui-Hsuan Lau; Cheng-Yuan Lai; Ming-Chun Hsieh; Hsien-Yu Peng; Dylan Chou; Tsung-Hsien Su; Jie-Jen Lee; Tzer-Bin Lin (Bioengineering)
The objective benefit of transvaginal mesh with concomitant total hysterectomy (TVM-HTX) repair to high-grade uterine prolapse (UP) patients has not been fully established. This study aimed to clarify the impact of TVM-HTX on the voiding function of high-grade UP patients by comparing pre- and post-operatively measured pressure–flow and pressure–volume investigations. Urodynamic and thermodynamic studies were conducted on 15 high-grade UP patients (stage III/IV, POP-Q system) who underwent TVM-HTX (January 2019–December 2022) in a tertiary-care university hospital. The parameters analyzed included voiding resistance (Rvod), voiding pressure (Pvod), voiding flow (Fvod), voided volume (Vvod), voiding time (Tvod), and the trajectory-enclosed area of the pressure–volume loop (Apv). Post-operative results showed a significant reduction in Rvod (p < 0.001, N = 15), Pvod (p = 0.021, N = 15), and Apv (p = 0.006, N = 15), along with an increase in Fvod (p = 0.003, N = 15) and a decrease in Tvod (p < 0.001, N = 15). The operation-associated changes in Rvod (ΔRvod) correlated with alterations in Pvod and Fvod (ΔPvod and ΔFvod, r = 0.444, p = 0.004, r = 0.717, p = 0.003, respectively; both N = 15); ΔFvod correlated with the change in Tvod (ΔTvod, r = 0.629, p = 0.012, N = 15) but not with that in ΔVvod (r = 0.166, p = 0.555, N = 15). Changes in Apv (ΔApv) correlated with ΔPvod (r = 0.563, p = 0.029, N = 15) but not with ΔVvod (r = 0.353, p = 0.197, N = 15). Collectively, TVM-HTX reduced the voiding resistance, which improved the voiding efficacy and decreased the pressure gradient required for driving urine flow, thereby lessening the bladder’s workload.